Santa Maradona: agiografia di un calciatore. - Alessandro Perissinotto (Funes)
In 2001, the movie Santa Maradona, directed by Marco Ponti, was released. Its title was taken from the song of the same name by Mano Negra. The movie make no mention of Maradona and this is, paradoxically, the most interesting aspect for an investigation into the role of the Argentinean superstar in the popular imagination, because the simple evocation in the title allows the director to create a paradigmatic link  between his characters and a real person who has now become an exemplary character in human comedy, Maradona. Like the saints in the medieval exempla, El Pibe de Oro is the one who falls into sin, but who never ceases to point out an exemplary path of redemption and redemption. This essay proposes to analyse the "secular sanctification" of Diego Armando Maradona, a process of beatification that had already begun during his life and, forcibly, accelerated the day after his death.